Fat Embolism and Nonconvulsive Status Epilepticus - Yanetsy Olivera Arencibia; Mai Vo; Jennifer Kinaga; Jorge Uribe; Gloria Velasquez; Mario Madruga; S. J. Carlan (Case Reports in Neurological Medicine)
Fat embolism syndrome (FES) typically occurs following orthopedic trauma and may present with altered mental status and even coma. Nonconvulsive status epilepticus is an electroclinical state associated with an altered level of consciousness but lacking convulsive motor activity and has been reported in fat embolism. The diagnosis is clinical and is treated with supportive care, antiepileptic therapy, and sedation. A 56-year-old male presented with altered mental status following internal fixation for an acute right femur fracture due to a motor vehicle accident 24 hours earlier. Continued neuromonitoring revealed nonconvulsive status epilepticus. Magnetic resonance imaging of the brain showed multiple bilateral acute cerebral infarcts with a specific pattern favoring the diagnosis of fat embolism syndrome. He was found to have a significant right to left intracardiac shunt on a transesophageal echocardiogram. He improved substantially over time with supportive therapy, was successfully extubated on day 6, and discharged to inpatient rehabilitation on postoperative day 15. Fat embolisms can result in a wide range of neurologic manifestations. Nonrefractory nonconvulsive status epilepticus that responds to antiepileptic drugs, sedation, and supportive therapy can have a favorable outcome. A high index of suspicion and early recognition reduces the chances of unnecessary interventions and may improve survival.